THE EFFECTS OF CONCEPT MAPPING LEARNING STRATEGY ON CIVIL ENGINEERING STUDENTS’ IN ENGLISH READING COMPREHENSION - Rasyidah, Ummi; Mardiansyah, Dedi (Edu Research, 2015)
This study extends the knowledge garnered with civil engineering populations by determining the reading comprehension strategies most important to students’ success on adult literacy outcome measures and aligning them with previously researched interventions. Concept Mapping should benefit from strategies that teach looking for clues in or generating questions about a text. A pre-experimental design is used. The result showed that post-test is higher than pre-test. It means that there is an improvement of students’ reading comprehension achievement who are taught byConcept Mapping Strategy.